THE USE OF SONG TO INCREASE STUDENTS’ VOCABULARY AT SEVENTH GRADE OF SMP NEGERI 1 SIAU TIMUR SELATAN - Belinda Gereuw; Meity Muntuuntu; Maikel Sanger (Program Studi Pendidikan Bahasa Inggris, 2022)
The aim of this study is to increase students’ vocabulary by using songs techniques of SMP Negeri 1 Siau Timur Selatan. The method used in this study was the pre-experimental method. This research was carried out in one class, namely the seventh grade with a total of 21 students. The students are taught using the songs and they are That is a Window, Things in the classroom and My Classroom. The instruments used in this study were pre-test and post-test. Mean score formula was used in analyzing data. The result showed that the pre-test score is 4,47 while the post-test score is 7,57. That means, Song is the right technique to use in increasing students’ vocabulary.